Mediating data protection breaches and disputes: the PDPA 2010 perspective - Zulhuda, Sonny (Kuala Lumpur Regional Centre for Arbitration (KLRCA), 2015)
The Personal Data Protection Act (PDPA) 2010 which was officially enforced in November 2013 had transformed organizations’ legal and governance landscape in relation to the processing and management of personal data within their internal and external business processes. One of the critical areas a data user needs to anticipate is on how to deal with incidents of data protection breach. Data protection breach – widely defined as the occurrence of non-compliance of the PDPA – is more than data security breach. It may happen in relation to the collection, storage, disclosure as well as retention of personal data.